The Molting Biomarker Molecule Exists as 2‐Acetamido‐2‐deoxy‐gluconic Acid in Urine of Blue Crabs and Helmet Crabs. Issue 9 (2nd September 2017) - Kamio, Michiya; Nagakura, Yasuhiro; Yano, Hirona
Abstract : N ‐Acetyl‐d ‐glucosamino‐1, 5‐lactone1 has been reported as a candidate component of the sex pheromone mixture of female blue crabs, Callinectes sapidus, since it is present in the urine of reproductive females and males detect it. Theoretically, 1 can convert to a 1, 4‐lactone isomer2 or to the corresponding carboxylic acid, 2‐acetamido‐2‐deoxygluconic acid3 by hydrolysis in aqueous solution. In this study, we examined the biologically relevant state of equilibrium mixture of1, 2, and3 in crab urine using ESI‐MS and NMR analyses. The ESI‐MS analysis showed that the dominant form of solubilized synthetic1 is lactone1 and/or2, immediately after solubilization in deuterated water, seawater, and phosphate buffer and gradually changing to carboxylic acid3 which becomes most predominant in phosphate buffer. The NMR analysis showed that synthetic1 converts to other forms in deuterated water and seawater, and reaches an equilibrium mixture of at least three forms within 24 h. In contrast, 1 converts to a single state of another form in deuterated water with 35 mm phosphate buffer pH 7.6 within 24 h, which is identical to the state in urine with or without phosphate buffer. Thus, we conclude that the molting biomarker sensed by male crabs is3 . Abstract : The Molting Biomarker Molecule Exists as 2‐Acetamido‐2‐deoxy‐gluconic Acid in Urine of Blue Crabs and Helmet Crabs M. Kamio*, Y. Nagakura, H. Yano